Communication between DNA polymerases and Replication Protein A within the archaeal replisome - Markel Martínez-Carranza; Léa Vialle; Clément Madru; Florence Cordier; Ayten Dizkirici Tekpinar; Ahmed Haouz; Pierre Legrand; Rémy A. Le Meur; Patrick England; Rémi Dulermo; J. Iñaki Guijarro; Ghislaine Henneke; et al. (Nature Communications)
Abstract Replication Protein A (RPA) plays a pivotal role in DNA replication by coating and protecting exposed single-stranded DNA, and acting as a molecular hub that recruits additional replication factors. We demonstrate that archaeal RPA hosts a winged-helix domain (WH) that interacts with two key actors of the replisome: the DNA primase (PriSL) and the replicative DNA polymerase (PolD). Using an integrative structural biology approach, combining nuclear magnetic resonance, X-ray crystallography and cryo-electron microscopy, we unveil how RPA interacts with PriSL and PolD through two distinct surfaces of the WH domain: an evolutionarily conserved interface and a novel binding site. Finally, RPA is shown to stimulate the activity of PriSL in a WH-dependent manner. This study provides a molecular understanding of the WH-mediated regulatory activity in central replication factors such as RPA, which regulate genome maintenance in Archaea and Eukaryotes.